2017
DOI: 10.1038/s41598-017-17417-8
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of the impact of universal added sugar reduction through food reformulation

Abstract: Food reformulation has been suggested to be one of the strategies to reduce population added sugar (AS) intake. This study aims to investigate the untested assumption that a reduction in AS through reformulation will result in a reduction in population intakes of AS and energy. Plausible dietary data from 4,140 respondents of an Australian national nutrition survey were used. Dietary modelling was performed at AS reductions of 10%, 15%, and 25% using four strategies: simple removal of AS or replacement with no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…Overall, studies were heterogeneous in the way interventions and outcomes were modelled and reported, limiting between-study comparisons. As regards the type of nutrient reformulated, 20 studies focused exclusively on sodium reduction (60.6%) [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41], followed by 5 studies considering at least 2 different nutrients (15.1%) [8,[42][43][44][45], 5 studies addressing sugar (15.1%) [46][47][48][49][50] and 3 study addressing fat (9%) [11,51,52].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, studies were heterogeneous in the way interventions and outcomes were modelled and reported, limiting between-study comparisons. As regards the type of nutrient reformulated, 20 studies focused exclusively on sodium reduction (60.6%) [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41], followed by 5 studies considering at least 2 different nutrients (15.1%) [8,[42][43][44][45], 5 studies addressing sugar (15.1%) [46][47][48][49][50] and 3 study addressing fat (9%) [11,51,52].…”
Section: Resultsmentioning
confidence: 99%
“…Four studies provided estimates for more than one item [8,[28][29][30], whereas in 4 studies target foods were not specified since reformulation was modelled directly through its assumed effect on intake [22,25,32,39]. Ten studies simply estimated changes in intake following reformulation (30.3%) [8,11,26,33,42,43,45,49,50,53], whereas other studies estimated effects on health outcomes (n = 12, 36.4%) [25, 31, 35, 37, 39-41, 44, 46-48, 51] or health related quality of life measures (n = 11, 33.3%) [22-24, 28-30, 32, 34, 36, 38, 52].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The extremely high average content of free sugars in ultra-processed food items suggest that reducing the content of sugars in packaged foods through reformulation, as currently in discussion in Australia [25], while potentially useful [26], may not solve the problem of excessive free sugars intake. Reformulation policies may also drive consumers towards consuming other ultra-processed foods [27], such as those that might not be included in the national reformulation program [25], or to artificially sweetened drinks [28].…”
Section: Discussionmentioning
confidence: 99%
“…The direction, magnitude and the statistical significance of the associations between the dietary share of ultra-processed foods and the risk of non-recommended intake levels of all studied nutrients did not change with adjustment for age, sex, educational attainment, socioeconomic status and geographical location. We also categorised individuals with diet energy density higher than 1.25 kcal/g (World Cancer Research Fund recommends lowering this value as a public health goal) (26) and the proportion of non-recommended intake levels increased from 82% to 98% from the lower to the upper quintile (PR: 1.2; p<0.001data not shown).…”
Section: Tablementioning
confidence: 99%